THU0186 Rheumatoid arthritis and interstitial lung disease. multicentric retrospective study of 118 patients treated with biological no anti tnf. (12th June 2018) - Fernández-Díaz, C.; Castañeda, S.; Garcia-Magallon, B.; Narvaez-García, J.; Retuerto, M.; Perez-Sandoval, T.; Martin-Lopez, M.; Rubio-muñoz, P.; Carrasco-Cubero, M.; Reina-Sainz, D.; Urruticoechea, A.; Ojeda-Garcia, C.; et al.
Abstract : Background: Interstitial lung disease (ILD) associated with Rheumatoid Arthritis (RA) has a poor prognosis. Treatments such as anti-TNF, have been implicated in the exacerbation of an ILD. Objectives: Our objective is to evaluate and compare the evolution of ILD in patients with RA treated with Abatacept (ABA), Rituximab (RTX) and Tocilizumab (TCZ) after 1 year of treatment. Methods: Retrospective multicentre study of patients with ILD and AR treated with ABA, RTX and TCZ at standard doses. The ILD was diagnosed by CT. The efficacy was evaluated whith the following measures: i) Dyspnea by modified scale of the Medical Research Council (mMRC); considering variations of 1 point. ii) Respiratory function tests; considering variations in FVC and DLCO ≥10%. iii) Imaging test (CT). Results: We included 118 (72 women/46 men) patients, mean age of 62.27±10.55 years. The ILD had a median evolution of 12 12–37 months. The RA was ACPA+in 102 cases (86.4%). At diagnosis, the mean DLCO onset of biological treatment was 65.63±19.38. Table 1 shows the characteristics by subgroups. The Figure expresses the evolution in the cases available at 12 months. There is an improvement in CT in 36.4% of patients with ABA, 28.6% of patients with RTX and only 8.3% of patients with TCZ. Conclusions: There seems to be a trend towards a better radiological response in patients treated with RTX and ABA. It would be necessary prospective studies. Disclosure of Interest: None declared